UTAUT AND DIGITAL TRANSFORMATION OF MSMEs: A STUDY ON FINTECH ADOPTION IN SURABAYA CITY - Agus Samekto; Diah Eka Kurniawati (Center for Indonesian Accounting Studies, 2025)
Research Objective – This study aims to understand the acceptance of Financial Technology (fintech)-based applications by Micro, Small, and Medium Enterprises (MSMEs) in Surabaya using the Unified Theory of Acceptance and Use of Technology (UTAUT) framework. Method – This research employs a quantitative approach with a population consisting of MSME actors in Surabaya. The sample comprised 107 respondents who are MSME owners or employees that have utilized fintech applications in their business activities. Data were collected through questionnaires and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). Theoretical and Policy Implications - The findings reveal that performance expectancy and social influence significantly affect behavioral intention to use fintech applications, while effort expectancy does not. Furthermore, behavioral intention and facilitating conditions have a significant influence on actual usage behavior. Research Novelty – The originality of this study lies in its comprehensive application of the UTAUT model within the context of fintech acceptance by MSMEs in a metropolitan city in Indonesia—an area still scarcely explored. The novelty is reflected in empirical findings that map the priority factors driving fintech adoption among MSMEs, highlighting the dominant roles of performance expectancy and social influence in shaping usage intentions.